Effect of pomegranate (Punica granatum L.) juice on kidney, liver, heart and testis histopathological changes, and the tissues lipid peroxidation and antioxidant status in lead acetate-treated rats - Aksu, D. S.; Sağlam, Y. S.; Yildirim, S.; Aksu, T. (Cellular and Molecular Biology, 2017)
Pomegranate juice (PJ) contains relevant amounts of active biological compounds which alleviate the detrimental effects of chronic heavy metal exposure. This study investigated the protective potential of PJ against lead-induced oxidative stress. A total of forty adult male Sprague Dawley rats were divided into four experimental groups. The animals were fed a standard pellet diet and tap water ad libitum. The rats were divided into four groups (n=10 for each group): control, lead asetat (2000 ppm), low-treated PJ- a daily dose of 2.000 ppm lead plus 30µl pomegranate juice (included 1.050 µmol total polyphenols, gallic acid equivalent), and high-treated PJ- a daily dose of 2.000 ppm lead plus 60µl pomegranate juice (included 2.100 µmol total polyphenols, gallic acid equivalent). The treatments were delivered for 5 weeks. After the treatment period, the tissues samples (kidney, liver, heart and testis) were collected. Tissue lead (Pb) and mineral amounts (copper, zinc, and iron), tissues lipid peroxidation level and antioxidant status, and tissues histopathological changes were determined. The results showed that the highest rate lead loading was in the kidney and the testis. Pomegranate juice was decreased the lead levels of soft tissues examined; increased Zn amounts in tissues of which the lead accumulation was higher (kidney and the testis); decreased the copper, zinc and the iron levels of the liver and heart tissues, without creating a weakness in antioxidant capacity of these tissues, restricted the oxidative stress by decreasing lipid peroxidation, improved both of the activities of antioxidant enzymes such as superoxide dismutase (SOD) and catalaz (CAT), and the level of glutathione (GSH) in all the tissues examined in lead-treated groups. As histopathological findings, the cellular damage induced by lead in the tissues of the kidney, liver and the heart were observed to have been partially prevented by PJ treatment. The protective effect of PJ was more pronounced in the testis compared to those others.